Coordination Analysis of Overcurrent Relays (OCR) and Directional Ground Relays (DGR) for Transformer Protection at Segoromadu Substation, Gresik - Puji Slamet; Reza Sarwo Widagdo; Aris Heri Andriawan; Muhammad Al Ahyudi (LPPM Universitas PGRI Adi Buana Surabaya, 2024)
Transformers are vital components in the distribution of electrical energy that are susceptible to overcurrent and short circuit disturbances, especially in substations. In this study, an analysis of the coordination of Over Current Relay (OCR) and Directional Ground Relay (DGR) was conducted to protect transformers in the Segoromadu Substation, Gresik. This analysis aims to determine the optimal settings of OCR and DGR, as well as to test the reliability of protection rather than safety equipment. Measurements were made by calculating the short circuit current of three phases, two phases, and one phase to ground, as well as the relay time settings. The simulation results show that the right settings on OCR and DGR can improve the reliability and safety of the substation protection system in maintaining a stable energy supply. These findings provide an important contribution in improving the performance of the protection system and can be a reference for the development of protection systems in other substations.